The Effects of Neoadjuvant Chemotherapy on Pulmonary Structures: A Quantitative Analysis - Ceylan, K. C.; Kaya, S. O.; Samancilar, O.; Gursoy, S.; Ucvet, A. (The Thoracic and Cardiovascular Surgeon, 2012)
Background The effects of neoadjuvant therapy on perioperative and postoperative outcomes of patients with stage IIIA non-small cell lung cancer remain controversial. We investigated histopathological changes possibly caused by neoadjuvant chemotherapy and their effect on the tensile forces of pulmonary structures.Methods A prospective study of 30 patients who had undergone lung resection was performed. The patients were divided into two groups. Group 1 included those who received neoadjuvant chemotherapy, and Group 2 included those who underwent surgery alone. Tensile stress tests were performed on freshly excised vascular and bronchial strips after lung resection. The pulmonary artery, veins, and bronchi that had not been invaded by the tumor were histopathologically examined in both groups. Intraoperative and postoperative complications were recorded.Results This study showed that the tensile strength of pulmonary vessels and bronchi was less in the neoadjuvant group than in the control group. There were statistically significant differences in the tissue strips obtained from arteries, veins, and bronchi between the two groups. In the chemotherapy group, most cases exhibited extensive fibrosis. There was no statistically significant difference in complications between the groups.Conclusions Neoadjuvant chemotherapy did not increase postoperative morbidity or mortality. The decreased tensile strength of pulmonary vessels and bronchi after neoadjuvant therapy should alert thoracic surgeons to possible surgical complications.
Keywords: lung cancer treatment (surgery, medical); chemotherapy; surgery, complications; neoadjuvant therapy; lung cancer; oncologic surgery